A study of IP-based vehicular gateway with IPv6. (2018) - Yu, He; Qin, Guihe; Sun, Minghui; Yan, Xin; Wu, Xingchen
With the progress of ambient sensor networks (ASNs), there is a trend that each node in ASNs should gather information and the server will supply intelligent service for users by processing and analysing the information. In order to achieve this purpose, each node and server must communicate with each other freely. IPv6 lets any host generate a unique IP address and supply far more addresses than IPv4. Therefore, it is necessary to migrate the IP address of each node from IPv4 to IPv6. As a proof-of-concept, we use the vehicle as an example. We propose the design and implementation of an IPv6-based in-vehicle gateway (IVG) and achieve end-to-end access between IPv6-based controller area network (CAN) unit and Ethernet. We use tunnel technology solve the issue through IPv4 to IPv6, develop address mapping method, and implement this notion by a prototype vehicle.